The effect of the Needham model on achievement and development of mental motivation among the students of the fifth- literary grade in the subject history - Ibrahim Mohamed, Hanaa (International Journal of Psychosocial Rehabilitation, 2020)
The current research aims to find out after Needham's model of achievement and mental motivation development among fifth-grade literary students in history by verifying the following zero hypotheses:1- There is no statistically significant difference at the indicative level (0.05) between the average grades of experimental group students studying the subject of modern and contemporary European and American history according to the Needham model and the average grades of female students of the control group studying the same subject in the usual way in the distance collection test.2- There is no statistically significant difference at the indicative level (0.05) between the average grades of experimental group students studying the subject of modern and contemporary European and American history according to the Needham model and the average grades of female students of the control group studying the same subject in the usual way in the distance collection test.3- There is no statistically significant difference at the level of significance (0.05) between the average grades of female students in the experimental group studying the subject of the history of modern and contemporary Europe and America according to the Needham model in the tribal and remote applications of the mental motivation scale4- There is no statistically significant difference at the indicative level (0.05) between the average grades of female students of the control group studying the subject of the history of modern and contemporary Europe and America according to the usual method in the tribal and remote applications of the mental motivation scale.